Analisis Hukum Pemberian Remisi Terhadap Narapidana Tindak Pidana Korupsi: Legal Analysis of Remission for Prisoners Convicted of Corruption - Syah, syawal Amirul; Asrullah Dimas; Mirnayanti; Sri Hasrina; Inda Sari Palinrungi; Nur Akifah Janur (Sekolah Tinggi Agama Islam Negeri Majene, 2025)
This study aims to analyze the juridical aspects of granting remissions to prisoners convicted of corruption crimes, focusing on the legal requirements and their alignment with Indonesian law. The primary questions addressed include the conditions under which remissions are granted, particularly within a moratorium framework, and how these legal regulations synchronize with other relevant laws in Indonesia’s legal system. The research employs a normative legal methodology, reviewing relevant legal materials, theories, principles, and regulations related to the issue. The main findings reveal that the legal requirements for remissions are stipulated in several government regulations, with notable differences between criteria for ordinary and extraordinary crimes, specifically for corruption offenses where stricter conditions are applied, complicating prisoner eligibility. Additionally, legal inconsistencies exist because the moratorium on remission for corruption prisoners conflicts with constitutional provisions and human rights laws. The study emphasizes the urgent need to revise existing regulations to prevent unconstitutional policies, advocating that the government, especially the Ministry of Law and Human Rights, should adhere to principles of correctional principles and human rights in the formulation of policies regarding prisoner development. The results contribute to ongoing debates on legal reforms and the protection of human rights within Indonesia’s correctional system, highlighting the importance of harmonized legal frameworks that respect constitutional and human rights standards.